Endocannabinoids and Dopamine Balance Basal Ganglia Output - Gorodetski, Lilach; Loewenstern, Yocheved; Faynveitz, Anna; Bar-Gad, Izhar; Blackwell, Kim T.; Korngreen, Alon (Frontiers in Cellular Neuroscience, 2021)
The entopeduncular nucleus is one of the basal ganglia's output nuclei, thereby controlling basal ganglia information processing. Entopeduncular nucleus neurons integrate GABAergic inputs from the Striatum and the globus pallidus, together with glutamatergic inputs from the subthalamic nucleus. We show that endocannabinoids and dopamine interact to modulate the long-term plasticity of all these primary afferents to the entopeduncular nucleus. Our results suggest that the interplay between dopamine and endocannabinoids determines the balance between direct pathway (Striatum) and indirect pathway (globus pallidus) in entopeduncular nucleus output. Furthermore, we demonstrate that, despite the lack of axon collaterals, information is transferred between neighboring neurons in the entopeduncular nucleus via endocannabinoid diffusion. These results transform the prevailing view of the entopeduncular nucleus as a feedforward "relay" nucleus to an intricate control unit, which may play a vital role in the process of action selection.